Impact of Concrete Sealer and Salt Usage on Concrete Bridge Deck Condition and Life Cycle Cost - Wei Huang; Hao Wang; Danny Xiao (Infrastructures)
The objective of this study is to analyze bridge deck condition deterioration and evaluate the impact of concrete sealer and salt usage on deck condition and life-cycle cost. To achieve this goal, machine learning models were built to predict the evolution of bridge deck rating. The deck maintenance history shows that the average bridge age at deck overlay and deck replacement is around 25 and 50 years, respectively. Deck overlay can improve deck condition from an average rating of 6.3 to 7.1, and deck replacement can efficiently recover deck condition from an average rating of 5.3 to 8.5. The effect of concrete sealer on bridge deck condition is only observable at the stage before the first overlay, indicating that concrete sealer may not be effective over the long term. More usages of prewet salt and salt brine in anti-icing result in slightly higher deck condition ratings, while more dry salt in deicing presents slightly lower deck condition ratings, indicating the benefits of salt brine over dry salt. When concrete sealer is applied every 2 or 4 years, it can help extend the service life of the bridge deck by around 1~2 years. If concrete sealer is applied every 12 years, a 6% reduction in life cycle cost could be achieved.